The rogue to ruin - Lorret, Vivienne (Lorret, Vivienne. Misadventures in matchmaking., 2019)
"Ainsley Bourne needs the family business to succeed. But one obstacle stands in her way--Reed Sterling, the huge, handsome, former prize fighter and owner of the gaming hall across the street. His scandalous customers scare off all her marriage-minded patrons and since the devilish brute has no intention of relocating, she sets out to ruin his unsavory establishment. Yet when a vile suitor from her past reappears, Ainsley hastily claims an attachment to the first man who comes to mind . . . Mr. Sterling, to be exact. Reed doesn't know who is more surprised by Miss Bourne's declaration. She clearly hates him, and he'd never admit their arguments simmer with unrequited attraction. Something about the pleading look in her eyes calls to Reed, and against his better judgment, he quickly plays the part of the besotted fiancé. Pretending to be in love requires a convincing charade. But with each tantalizing touch and every scandalous kiss, Ainsley starts to wonder if Reed was ever really the enemy at all."--Back cover.